DISIPLIN BELAJAR SISWA SD SAAT PEMBELAJARAN DARING DALAM PERSPEKTIF GURU - Rika Nurhidayah; J. Julia; Dadan Nugraha (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
The existence of a pandemic has changed the learning process, which is usuallyimplemented face-to-face between teachers and students at schools become online learningfrom home. The study described in this article aims to investigate the learning discipline of elementary school (SD) students during online learning, either in the village or city based on the teacher's perspective. The research method used was a qualitative approach with a case study design. Data collection used interviews and recording methods. The research instrument used was an interview guide, google form, and a recording device by cell phone. The participants involved three elementary school teachers who taught in the village and three elementary school teachers who taught in the city. The results of data collection were then analyzed and produced five themes, which were (1) discipline of time and actions (2) students’ learning activities, (3) differences in learning disciplines, (4) efforts and teacher cooperation, and (5) efficiency of cultivating learning disciplines. The results showed that based on the teacher's perspective, students' learning discipline during online learning changed in various aspects, in fact, not significantly, only influenced a small number of students in the class. However, teachers overall considered that the learning discipline during online learning tends to be less, thus, it is better to implement face-to-face learning at school. It was implemented either for elementary schools in the village or urban areas.